Wear behavior of a crankshaft journal bearing manufactured by powder spraying - Nursoy, Mustafa; Oner, Cengiz; Can, Ibrahim (Elsevier Sci Ltd, 2008)
A new crankshaft bearing material that can be an alternative to the traditional material has been improved and its wear behavior studied experimentally. Crankshaft main bearings are subjected to various stresses. A new material supposed to be adapted these operating conditions was designed composing of Pb-Sn-Cu-ZrO(2) and manufactured by HVOF spraying technique. Wear behavior of the bearing was tested with the simulation of real operating conditions. An original bearing was used for comparison. After a trial of 500 h, the weight losses were measured. SEM micrographs of both original and new bearings were examined. The effect of microhardness was discussed. The new composition was seen as promising as a bearing material for automotive engines. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: crankshaft bearing material; powder spraying; wear